A Novel Hybrid and Secure Clustering Black hole Attacks Mitigation Technique in Wireless LAN - Harmeet Singh, Er.; Vijay Dhir, Dr. (International Journal of Engineering and Technology, 2018)
Wireless LAN is a dynamic network with large number of mobile nodes. As the traffic increases over the wireless, it will lead to number of problems like congestion and packet loss. This congestion and packet loss problems occurs due to the attacks in wireless LAN.Out of the various attacks black hole attack is most dangerous attack which drops all of the packets received from the source node and which act as a black hole in the universe. In this paper we are providing solution against this attack. We propose a Novel Hybrid and Secure Clustering Black hole Attack Mitigation Technique in Wireless LAN. This technique firstly detects the black hole attack by using threshold values against different parameters, after this clustering approach is used for secure path from source to destination by reducing overhead in the network. Most of existing mechanisms are not as efficient because by isolating black hole attack overhead is increased. A HSBM approach has remarkable advantage over these existing techniques. We simulate the proposed technique by using NS2 simulator and proved that our technique effectively detects the black hole attack in terms of throughput, packet loss, end to end packet delivery ratio, delay.Â Â